2014
DOI: 10.7441/joc.2014.03.04
|View full text |Cite
|
Sign up to set email alerts
|

Customer Relationship Management Approach and Student Satisfaction in Higher Education Marketing

Abstract: The primary objective of the article was to determine the relationship between customer relationship management and student satisfaction. The study explored the ways in which student satisfaction can be achieved with the use of customer relationship management. Both descriptive and inferential statistics were employed in this research. The following hypotheses were formulated in this study: Student Lifecycle management has a significant impact on the student's willingness to recommend to others, Parent relatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 12 publications
0
13
0
3
Order By: Relevance
“…Oluseye, Tairat, and Emmanuel (2014) [38] reported that business corporate decision makers are aware that excellent customer service is critical to building relationships with customers. The concept of relationship marketing is for organizations' staff to develop relationships with customers by providing excellent customer service and satisfaction beyond advertising and sales [21].…”
Section: Customer Service Philosophymentioning
confidence: 99%
“…Oluseye, Tairat, and Emmanuel (2014) [38] reported that business corporate decision makers are aware that excellent customer service is critical to building relationships with customers. The concept of relationship marketing is for organizations' staff to develop relationships with customers by providing excellent customer service and satisfaction beyond advertising and sales [21].…”
Section: Customer Service Philosophymentioning
confidence: 99%
“…Students being dissatisfied and cannot focus on their study. In addition, the academic programs are stopped, giving students' undeserved extension in their study years, poor students' concentration on academic programs and the relationships between teachers or lectures and students were not useful and dissatisfied [1].…”
Section: Customer Relationship Management and Educational Systemmentioning
confidence: 99%
“…CRM has recently become one of the most controversial issues and a focal point in the business field [1]. It is worth mentioning that CRM is mainly based on the belief that establishing a sustainable relationship with customers is the cornerstone for obtaining loyal customers who are much more profitable than non-loyal ones [2].…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, on the subject of learning environment, HEIs staff members who are kind, considerate and responsive, lecturers with better teaching quality [30] and the ability of faculty members to create a classroom that supports multicultural diversity [31] will create a progressive and better learning environment and higher quality of education, which, eventually will lead to a higher level of students" satisfaction. Students who are satisfied with the teaching quality and the HEIs management would likely promote the institution in the future [5], [32]. Consequently, it is hypothesized that:…”
Section: B Hypotheses Developmentmentioning
confidence: 99%